STUDY OF ORIENTAL MINIATURE SCHOOLS IN FINE ARTS AND ENGINEERING GRAPHICS (Academicia Globe: Inderscience Research, 2024)
This article provides scientific information about the study of Eastern miniature schools in the field of fine arts and engineering graphics.